Closing the educational gap for first generation learners: an exploratory study of interactive learning for underprivileged children in India - Swaralipi Roy Chowdhury Samanta; María Victoria Soulé (Tecnología, Ciencia y Educación)
Previous research studies have indicated that interactive tools where information is presented through computer mediated technology using elements like text, still images, graphics, animation, video, audio, etc., increase student performance as students (men and women) give more attention and enjoy lessons taught with interactive tools. In India, an increasing number of students belonging to disadvantaged classes withdraw from schools due to a lot of contributing factors such as inability to afford education, disinterest of parents, access to transportation, etc. This study, by applying a mix-methods approach, explores the potential of an interactive learning prototype of a website, in increasing engagement, retention and learning level of grade 4 students who are first generation students. In-class observation and semi-structured interviews, tests, and a questionnaire were used as instruments to collect qualitative and quantitative data from 58 participants. Two types of groups, experimental and control, were examined in the Environmental Science and Maths classes. Experimental groups were taught with the website while control groups were taught in a traditional class. Results show the average test scores of experimental groups in both the subjects to be higher than the control groups. Students preferred learning through interactive tools with colourful images and animations.